2020
DOI: 10.20945/2359-3997000000308
|View full text |Cite
|
Sign up to set email alerts
|

A single session of low-volume high-intensity interval and moderate-intensity continuous exercise elicits a transient reduction in ghrelin levels, but not in post-exercise energy intake in obese men

Abstract: Objective: This study investigated the acute effects of high-intensity interval (HIIE) and moderateintensity continuous (MICE) exercise on ghrelin levels in obese men. Subjects and methods: A total of 10 obese men (age 27.6 ± 1.8 years, body mass index 35.4 ± 4.5 kg/m², body fat 39.9 ± 2.1%) performed two exercise sessions in a randomized order: HIIE (10 x 1 min intervals at 90% of the maximal heart rate [HR max ] interspersed by 1 min of active recovery) and MICE (20 min at 70% of the HR max). Ghrelin levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A lack of ghrelin change was noted with short-term, long-term, or very long-term exercise of aerobic [46-51, 57, 69, 72, 74, 79, 83], resistance [53], combined [79], or intermittent [73] type. Five studies showed a decrease in trained [60,74,91] or untrained [59], normal weight or overweight/obese [69] individuals following short-or long-term aerobic [60,74], resistance [91] or intermittent [59,69] exercise. Finally, five studies involving active subjects showed an increase in TG following shortterm [50,71] or very long-term [94][95][96] moderate-intensity aerobic exercise.…”
Section: Response To Acute Exercisementioning
confidence: 99%
“…A lack of ghrelin change was noted with short-term, long-term, or very long-term exercise of aerobic [46-51, 57, 69, 72, 74, 79, 83], resistance [53], combined [79], or intermittent [73] type. Five studies showed a decrease in trained [60,74,91] or untrained [59], normal weight or overweight/obese [69] individuals following short-or long-term aerobic [60,74], resistance [91] or intermittent [59,69] exercise. Finally, five studies involving active subjects showed an increase in TG following shortterm [50,71] or very long-term [94][95][96] moderate-intensity aerobic exercise.…”
Section: Response To Acute Exercisementioning
confidence: 99%
“…More than half of the studies (n = 7) had low levels of attrition bias [ 16 , [21] , [23] , 26 , 27 , [36] , [37] ], while the other five studies resulted in unclear levels of attrition bias given that no sufficient information was provided [ 22 , 25 , 28 , [24] , [35] ]. Levels of reporting bias were low in five of the included studies [ 16 , 21 , 27 , [24] , [36] ], while it is unclear about the other seven studies [ [22] , [23] , [25] , [26] , 35 , [37] , [38] ]. Evaluations of the carry-over effect demonstrated low levels of carry-over effect in the majority of the studies (n = 11) since these studies provided one to two weeks of wash-over periods between the experimental session; one study did not provide information regarding the wash-over periods [ 16 ].…”
Section: Resultsmentioning
confidence: 99%